The Income Portfolio of Immigrants in Germany - Effects of Ethnic Origin and Assimilation Or: Who Gains from Income Re-Distribution? - Joachim R. Frick; Felix Büchel (Institute for the Study of Labor (IZA), 2000)
This paper deals with the economic performance of various population groups in Germany giving special attention to ethnic origin of immigrants as compared to the native born German population. In addition, winners and losers of the re-distribution process, induced by the tax and social security system, are identified. This is done by considering different components of market and non-market income as well as taxes and social security contributions. This income portfolio analysis is based on data from the German Socio-Economic Panel covering the observation years 1995 to 1997. Population subgroups are made up of West Germans, East Germans, and immigrants; the latter being split into Ethnic Migrants (Aussiedler) and foreigners. Immigrants are differentiated according to their state of assimilation: those immigrants living together with a native born adult German (?mixed? immigrants) and others (?pure? immigrants). In order to control for any retirement related impact we run all analyses for the total population as well as for those who live in households with a head of prime age. Our results show that immigrants are a very heterogeneous group with respect to their economic performance. The well-assimilated ?mixed? immigrants have an even better relative income position than the autochthonous West German population. In general, we confirm the well-known poor market performance of immigrants. However, also immigrants non-market incomes are atypically low (except for those of ?pure? Aussiedler), mainly due to their age structure, resulting in lower eligibility for and receipt of old age pensions. Non-market incomes of younger immigrants are somewhat higher than those of the autochthonous West German population, but still much lower when compared to the East German population.Analyzing the re-distribution effect caused by public transfers, old age pensions, and tax and social security contributions, we find that immigrants as a whole are (slightly) net payers. Again, ?pure? Aussiedler are an exception. When focusing only on younger people, the situation is reversed, and immigrants profit slightly. This is due to above average non-market income of ?pure? immigrants. However, East Germans are still much better off. The question which remains to be answered is whether these differences stem from an immigrant specific effect per se or whether they are influenced by underlying social structure differences. Using random-effects models to control for various socio-economic measures, we find that non-German immigrants remain net payers. In addition, immigrants? need of being subsidized by the re-distribution process rapidly and strongly decreases with progressing duration of stay in Germany. On the other hand, the subgroups substantially profiting from the re-distribution process are ?pure? Aussiedler and East Germans. This means –at least in our static ?snapshot? analysis– that the ?classic? immigrants (of non- German nationality) are no economic burden to the autochthonous population.
Keywords: 330; Immigration; migration policy; income; income re-distribution; Migranten; Einkommen; Aussiedler; Soziale Integration; Einkommensumverteilung; Schätzung; Deutschland